Fixation of Tibial Shaft Fracture by Interlocking Nail without Proximal Screws - Mondal, Anadi Ranjan; Uddin, Md Maiyeen; Akhter, Mohammad Shahin; Rahaman, Md Masudur; Alam, Syed Asif Ul; Karmakar, Narayan Chandra (Bangabandhu Sheikh Mujib Medical College Journal, 2023)
Tibia is the most commonly fractured long bone. In adults it takes 4 to 6 months to heal depending on the severity of injury and method of treatment. Rate of complications are also high. Locked intramedullary nailing is the preferred treatment for tibial shaft fractures. When locked proximally and distally, removal of one set of screws, especially in transverse and short oblique fractures are required for dynamization before weight bearing. Fail to do this timely, many of these patients present with nonunion and implant failure. The purpose of the study was to enhance healing of tibial shaft fracture by early weight bearing, at the same time minimizing the complications and early return to work. Stable open type- I, II & closed tibial shaft fractures from the isthmus to 4 cm above the distal articular surface of the tibia were fixed by locking nail without proximal screws. This prospective study was done from June 2009 to July 2014 on 410 patients treated at several hospitals of Faridpur city. All the operations were done in closed method without any C-Arm monitoring. Patients were allowed to move with crutch and controlled partial weight bearing within two to four weeks of operation. All patients were followed up for five years. In most cases the nail were removed in one to two years. Early weight bearing causes compression and intermittent micro movements at the fracture site. The fractures heal as early as in eight to twelve weeks and no nonunion or implant failure were encountered. Knee pain was complained by 41 patients (10%), disappeared after removal of the nail. Superficial infection developed in 8 cases (1.95%), controlled in 2 to 3 weeks and deep infections were encountered in 8 cases (1.95%) with delaying union but eradicated spontaneously as the fracture healed. Deep infection occurs only in open fractures. Although five years period is not enough to comment about development of secondary osteoarthritis, we encountered no such cases till now. So, closed reduction and internal fixation (CRIF) of stable open type-I, II & closed tibial shaft fractures from the isthmus to 4 cm above the distal articular surface of the tibia by interlocking nailing with distal locking screws only, allows early controlled weight bearing, thereby early fracture healing and less chance of implant failure. Bangabandhu Sheikh Mujib Med. Coll. J. 2022;1(1):33-36